E-Catalog Development and User Interface Design at PT. Madina Mentari Teknologi Using Figma: Pengembangan E-Katalog dan Desain Antarmuka Pengguna di PT. Madina Mentari Teknologi Menggunakan Figma - Wahyu Karobby; Istian Kriya Almanfaluti (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital transformation in the modern professional landscape necessitates that universities cultivate innovative, skilled, and technologically adept graduates. Specific Background: PT. Madina Mentari Teknologi, a provider of fintech and payment system solutions, requires a robust digital presence to improve product visibility and client engagement. Knowledge Gap: While the company offers sophisticated financial technology services, it lacked a comprehensive, interactive, and aesthetically intuitive e-catalog to effectively showcase its product portfolio to potential clients. Aims: This internship project aimed to develop a professional e-catalog and an intuitive user interface (UI) for the company's web platform, madinapay.co.id. Results: Utilizing Figma and a prototyping development method, the project successfully delivered a minimalist, flat-design-based e-catalog and a fully optimized website interface that integrates consistent color palettes, strategic typography, and responsive grid layouts to enhance user experience and engagement. Novelty: This study integrates modern UI/UX design principles with practical business requirements by creating a standardized design system that facilitates seamless navigation and improves information accessibility for fintech products. Implications: The developed interface and e-catalog serve as a strategic asset for the company, streamlining the browsing experience for clients, reducing information search time, and reinforcing the brand’s professional digital identity within the competitive technology sector. Highlights: Prototype development using cloud-based collaborative design tools significantly streamlines the iterative interface refinement process. Minimalist design principles and intuitive navigation structures are pivotal for improving information accessibility for fintech clients. Standardized design systems guarantee visual consistency while optimizing front-end development efficiency for complex web platforms. Keywords: E-Catalog, User Interface, Figma, Prototyping, User Interaction